2014
DOI: 10.1101/006023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restriction and recruitment - gene duplication and the origin and evolution of snake venom toxins

Abstract: The genetic and genomic mechanisms underlying evolutionary innovations are of fundamental importance to our understanding of animal evolution. Snake venom represents one such innovation and has been hypothesised to have originated and diversified via a process that involves duplication of genes encoding body proteins and subsequent recruitment of the copy to the venom gland where natural selection can act to develop or increase toxicity. However, gene duplication is known to be a rare event in vertebrate genom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Casewell (21) utilized phylogenetic analysis of viperid venom-expressed SVMPs to reveal the monophyletic origin of P-II SVMPs from a P-III SVMP ancestor, but P-I SVMPs appear to have arisen independently at least eight times from class P-II ancestors. The large number of SVMP proteins and their diverse activities have prompted many authors to suggest a role for gene duplication and sequence divergence during the expansion of advanced snakes (16,19,(22)(23)(24). In the king cobra (an elapid), Vonk et al (16) found two venom-expressed SVMPs adjacent to the ADAM28 locus and suggested that the two cobra SVMPs evolved by duplication from the ADAM28 ancestor.…”
Section: Significancementioning
confidence: 99%
“…Casewell (21) utilized phylogenetic analysis of viperid venom-expressed SVMPs to reveal the monophyletic origin of P-II SVMPs from a P-III SVMP ancestor, but P-I SVMPs appear to have arisen independently at least eight times from class P-II ancestors. The large number of SVMP proteins and their diverse activities have prompted many authors to suggest a role for gene duplication and sequence divergence during the expansion of advanced snakes (16,19,(22)(23)(24). In the king cobra (an elapid), Vonk et al (16) found two venom-expressed SVMPs adjacent to the ADAM28 locus and suggested that the two cobra SVMPs evolved by duplication from the ADAM28 ancestor.…”
Section: Significancementioning
confidence: 99%
“…Failing to account for this have multiple misleading effects, most notably regarding tests of the recruitment hypothesis (i.e. whether there has been one or multiple recruitment events, see [Casewell et al, 2012;Hargreaves et al, 2014b]) and the adequacy of selection tests performed on alignments merging both old and recent paralogs as these are likely to be influenced by the different evolutionary rates of both (see [Jordan et al, 2004;Aguileta et al, 2006;Pegueroles et al, 2013]) and affected by gene conversion leading to overestimation of positive selection [Casola and Hahn, 2009]. The quantitative differences between venom glands and pooled tissues expression of genes encoding toxin-like proteins in M. martensii and the restricted set of VZsame expressed genes in O.…”
Section: Relative Expression Of Genes Encoding Toxin-like Proteins Inmentioning
confidence: 99%
“…This gap motivates computational methods that can automatically and accurately identify venom peptides in the large protein datasets. The prediction of venoms versus non-venom sequences is not a trivial task protein classification task, where the use of BLAST-based approaches is challenging: venoms are often (i) evolved from non-toxic proteins (Hargreaves et al, 2014), (ii) and then have highly diverged (Linial et al, 2017). Several studies have proposed computational and machine learning-based methods for predicting or analyzing toxin/venom peptides (Cole and Brewer, 2019;Dao et al, 2017;Gacesa et al, 2016;Naamati et al, 2009;Ojeda et al, 2018;Pan et al, 2020;Wong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%